-0.99(h-7)=-7.92

Simple and best practice solution for -0.99(h-7)=-7.92 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -0.99(h-7)=-7.92 equation:


Simplifying
-0.99(h + -7) = -7.92

Reorder the terms:
-0.99(-7 + h) = -7.92
(-7 * -0.99 + h * -0.99) = -7.92
(6.93 + -0.99h) = -7.92

Solving
6.93 + -0.99h = -7.92

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '-6.93' to each side of the equation.
6.93 + -6.93 + -0.99h = -7.92 + -6.93

Combine like terms: 6.93 + -6.93 = 0.00
0.00 + -0.99h = -7.92 + -6.93
-0.99h = -7.92 + -6.93

Combine like terms: -7.92 + -6.93 = -14.85
-0.99h = -14.85

Divide each side by '-0.99'.
h = 15

Simplifying
h = 15

See similar equations:

| Xsquared+ysquared=153 | | -3(d-8.8)=6.3 | | 31(m-963)+63=931 | | 4x-12=20-4x | | 59=4x+27 | | 23000=10x | | a+3+2=-1+3a+4 | | 5x+21=2x+3 | | solvex+5=20-4x | | -x^3+9x^2+x-105=0 | | 8000*12=3000+(3000+x)+(3000+2x)+(3000+3x)+(3000+4x)+(3000+5x)+(3000+6x)+(3000+7x)+(3000+8x)+(3000+9x)+(3000+10x)+(3000+11x) | | x^3+9x^2+11x-34=-3x-10 | | 96000=3000+(3000+x)+(3000+2x)+(3000+3x)+(3000+4x)+(3000+5x)+(3000+6x)+(3000+7x)+(3000+8x)+(3000+9x)+(3000+10x)+(3000+11x) | | 2h+2s=3.50 | | 10=3x+12y | | 2.5(a+4)-3.2=43 | | 15x^4-10x^2=0 | | t-13=35 | | 5760000=x*(x+50) | | 4w-4=2w-11 | | 6.6+6n=7n-0.4 | | 2x+1=x+37 | | -104=8i | | 30x+(20-x)x=100 | | h-9=-13 | | f(x)=-1.5x+10 | | 4.5(7)+4.5(6)= | | -20=-4e-6e | | 270+230+240+250= | | 101.75*3.65= | | -8t=32 | | J-15=-27 |

Equations solver categories